An exploratory study of delayed flash visual evoked potential P2 wave latency in subcortical arteriosclerotic encephalopathy - Lei Duan; Yu Ding; Gao-hui Sun; Yun-tao Li (BMC Neurology, 2023)
Abstract Background Patients with cognitive dysfunction may present with significantly prolonged the P2 wave latency of flash visual evoked potential. However, no studies have been reported on whether the P2 wave latency of flash visual evoked potential is prolonged in patients with subcortical arteriosclerotic encephalopathy (SAE). Objective To examine the relationship between flash visual evoked potential P2 wave latency (FVEP-P2 wave latency) and cognitive impairment in patients with SAE. Methods Overall, we recruited 38 SAE patients as the observation cohort (OC) and 34 healthy volunteers as the control cohort (CC). We measured the FVEP-P2 wave latency for both groups. The SAE patients’ cognitive abilities were evaluated via mini-mental state examination (MMSE) and the association between the latency of FVEP-P2 and MMSE score was explored by Pearsons´s correlation test. Results There is no significant difference between OC (21 males and 17 females; 68.6 ± 6.7 years of age and 9.6 ± 2.8 years of education) and CC (19 males and 15 females; 65.3 ± 5.9 years of age and 10.1 ± 2.6 years of education) in gender and age composition and education level. The FVEP-P2 wave latency of the CC group was (108.80 ± 16.70) ms and the OC FVEP-P2 wave latency was (152.31 ± 20.70) ms. The OC FVEP-P2 wave latency was significantly longer than the CC (P < 0.05). In terms of MMSE scores, the MMSE scores of CC was (28.41 ± 2.34), and that of OC was (9.08 ± 4.39). Compared to the CC, the OC MMSE score was significantly lower (P < 0.05). In addition, the FVEP-P2 wave latency was inversely related to the MMSE (r = -0.4465, P < 0.05) in SAE patients. Conclusion The FVEP-P2 wave latency wave latency was significantly prolonged in SAE patients and strongly associated with the degree of cognitive dysfunction.